Poststrukturalizm, dekonstrukcja, feminizm, gender, dyskursy mniejszości i co dalej? - Burzyńska, Anna (Przestrzenie Teorii, 2007)
The article is a brief summary of the last critical phase in literary studies. It considers some most important meanings of prefix "post-" according to opinions of its inventor, the French philosopher Jean-Franęois Lyotard. Deconstruction, feminist criticism, gender studies, discourses of the minorities etc. - all these have a "postic" character, because they transform the petrified traditions into new forms, revealing their unnoticed possibilities, and stressing their critical resources. The author introduces to poststructuralism, one of the most important trends of the European and American postmodern thought (the critique of epistemological foundationalism), for which deconstruction built a philosophical background. The author stresses metatheoretical dimension of the poststructuralist thought.